THE THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, LEVERAGE, AND FREE CASH FLOW ON EARNINGS MANAGEMENT - Rifda Nadifah; Poppy Dian Indira Kusuma; Triani Arofah (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2020)
This study aims to determine the effect of CSR Disclosure, Leverage, and Free Cash Flow on profit management. The population in this study was manufacturing companies in the food and beverage sector which were listed on the Indonesia Stock Exchange (BEI) in the 2016-2018 period. Sampling was carried out using a purposive sampling method, and the number of samples used in the study was 26 data of food companies and drinks. Based on the results of research and data analysis using SPSS shows that: (1) CSR disclosure does not affect earnings management, (2) Leverage does not affect earnings management, and (3) Free cash flow does not affect earnings management. The results of this study imply that CSR disclosure is not the only indicator that is considered by investors. Investors may pay more attention to the company's prospects in the future along with the performance of the company. It is expected that companies can pay more attention to social responsibility as an effort to establish policies in promoting a balance between company profits and the benefits of society as a whole. Besides, in conditions where leverage and free cash flow are high, managers do not always think to undertake earning management to overcome the problems. Managers may consider the reversal impact after the earning management which may give a more negative impact on the company.